Desain Soal Cerita Matematika dengan Strategi Instruksional Solve It! Pada Materi Sistem Persamaan Linear Tiga Variabel - Wina Octaviani; Johannes Gultom; Nurul Bayyinah (Mandalika Mathematics and Educations Journal, 2025)
Problem-solving skills are an important aspect that students must acquire both in learning and in everyday life. This is in line with the high standards set by the CCSS that students must have the ability to reason and apply mathematical thinking to world problems and challenges. One way to measure and improve problem-solving skills in mathematics classes is by providing story problems. The purpose of this study is to analyze, design, and develop a product in the form of a mathematical story problem design using the Solve It! learning strategy on the material of three-variable linear equation systems. The research method used is design and development research (DDR). The product was designed and tested on students, then evaluated based on the results of the trials that have been carried out. The development used is testing at a higher level with the diversity and needs of students in inclusive classes. As well as using PISA standard mathematical story problems to train students' problem-solving skills with simple instructions at each step of the solution. The results obtained can equip mathematics teachers with a student worksheet model for teaching three-variable linear equation systems with appropriate strategies to improve the mathematical problem-solving skills of students with learning disabilities.